Objectively measured sedentary behaviour and moderate and vigorous physical activity in different school subjects: a cross-sectional study - Kerli Mooses; Katrin Mägi; Eva-Maria Riso; Maarja Kalma; Priit Kaasik; Merike Kull (BMC, 2017)
Abstract Background Evidence shows the positive influence of moderate and vigorous physical activity (MVPA) and negative influence of sedentary time on health and academic achievement. Although schools can significantly contribute to overall physical activity, little is known about MVPA and sedentary behaviour in different school subjects in different grades. Methods Physical activity of 646 students from 18 schools (94 classes) and from three school stages (grades 1-9, aged 7-16) was measured with accelerometry for 5 school days. Time and proportion of MVPA and sedentary time, also average sedentary bout length was calculated for native language (Estonian), mathematics, science, foreign language, music and crafts lessons. Results A total of 6363 lessons were measured, with lesson duration of 45 min. The average lesson time MVPA remained below 2.2 min in all school stages and in all subjects. Students in grades 4-6 had greatest decline in the proportion of lesson time MVPA in science (β = −1.9, 95%CI −3.1- -0.6) and music (−1.2, −2.1- -0.4) and in grades 7-9 in music (−1.7, −3.1- -0.3) lessons compared to grades 1-3. In grades 1-3 students spent on average 76% of lesson time (34.0 ± 7.0 min) as sedentary, whereas in grades 7-9 the average proportion of sedentary time was 87% (38.9 ± 5.7 min). An average sedentary bout length increased from 13 min in grades 1-3 to 20 min in grades 7-9. An increase in sedentary bout length from grades 1-3 compared to grades 7-9 was present in most subjects, except crafts, with smallest increase in foreign language (6 min, 3.5-8.9) and greatest in music lessons (16.6 min, 11.9-21.3). Lessons with prolonged sedentary bouts formed a maximum 36% of all lessons in grades 1-3 and 73% in grades 7-9. Conclusion The long sedentary time, bout length and low MVPA in most subjects were unfavourable in respect of both health and academic achievement. Significantly increasing sedentary time and sedentary bout length in older school stages highlights the need for interventions in all subjects and especially in older grades in order to combat the inactivity of children.